Análise de um conversor fonte de tensão a quatro fios com corrente de neutro gerada por cargas desequilibradas - Silva, Paulo Fernando (Universidade Federal de São Carlos, 2022)
Several studies have examined the reduction of carbon dioxide emissions into the atmosphere. The use of sustainable energy sources, such as solar and wind power, is focused by some of these studies. The Voltage Source Converter (VSC) is usually emplayed to connect solar photovoltaic systems to the electrical grid. The four-wire VSC enables the connection of three-phase four-wire grids to single-, two-, and three-phase loads in addition to providing a path for the load neutral current. The load neutral current is generated at the Point of Common Coupling (PCC), produced by unbalanced single- or three-phase loads. As confirmed in the literature, depending on the VSC application, the load neutral can be splitted into two parts, the midpoint and neutral currents, generating problems in the VSC and in its respective operations, such as voltage surge on the DC side of the VSC. The present study analyzes the midpoint current in four-wire VSC, operating as a follower and grid-former under unbalanced voltage in the PCC. The following were studied in this analysis: the four-wire VSC, application of the proportional-resonant controller in the VSC control system operating as a follower and grid-former, application of the filter between the point of the capacitors and the common point of the loads connected to the PCC. A literature review of the four-wire VSC and simulation results indicated that the midpoint current carries low amplitude frequencies that when interacting with capacitors on the DC side of the VSC promote voltage ripple across them.
Analysis of four-wire voltage source converter with neutral current generated by unbalanced loads
Keywords: Carga desequilibrada; Topologia do ponto médio do capacitor dividido; Corrente do ponto médio; VSC a quatro fios; Controlador proporcional-ressonante; Unbalanced load; Split capacitor midpoint topology; Midpoint current; Four-wire VSC; Proportional-resonant controller; ENGENHARIAS::ENGENHARIA ELETRICA::CIRCUITOS ELETRICOS, MAGNETICOS E ELETRONICOS